ANALISIS SELF EFFICACY DAN INTERDIALYTIC WEIGHT GAIN (IDWG) PADA PASIEN HEMODIALISIS: LITERATURE REVIEW - Akheri Ramadhanti (Yayasan Pendidikan Medika Indonesia, 2022)
Chronic kidney disease (CKD) is a global public health problem whose incidence is increasing, poor prognosis and high costs. Efforts that can be done in CKD patients are hemodialysis therapy. Hemodialysis is a high-tech replacement therapy as a substitute for kidney function for humans. A problem that often occurs in hemodialysis patients is an increase in interdialytic weight gain (IDWG) due to non-compliance of patients with a given diet. Patient adherence in the CKD diet can be influenced by self efficacy. This study aims to analyze the research articles on self efficacy and IDWG in patients undergoing hemodialysis. This research uses the Literature Review method. Source of data search for publication articles is done on google scholar, pubmed and science direct. The results of the study are based on 6 articles, the majority of hemodialysis patients are male. The results of the description of self efficacy based on the articles reviewed showed that the majority of respondents had high self efficacy. The results of the IDWG picture show that there are still many respondents who experienced an increase in IDWG even in the mild category.